Synthesis and fungicidal activity of 1-[(1H-1,2,4-triazol-1-yl)alkyl]-1-silacyclohexanes - Yoo, BR; Suk, MY; Yu, YM; Hong, SG; Jung, IN (KOREAN CHEMICAL SOC, 1998)
A series of six-membered ring organosilicon compounds, 1-aryl-1-(1H-1,2,4-triazol-1-yl)alkyl-l-silacyclo-hexanes 3a-c, have been synthesized by four-step reactions starting from 1-(chloroalkyl)trichlorosilanes. Their fungicidal activities were tested in in vitro for ten fungi and in vivo assay for four fungi occurring in rice, barley, tomato, and etc. and compared with the flusilazole. Especially, 1-p-nuorophenyl-1-[1-(1H-1,2,4-triazol-1-yl) alkyl]-1-silacyclohexanes (3a, alkyl=methyl; 3b, alkyl=methyl) showed good fungicidal activity with bread spectrum close to the flusilazole in in vivo assay.
Keywords: INSECTICIDES; REPLACEMENT; SILICON; CARBON